Health Worker Coping Strategies When Serving Patients During A Pandemic Situation - Fadhilah Ahmad Qaniah; Ahmad Ridha Muthmainnah (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
The purpose of this article is to explore the factors that make health workers continue to serve patients during the Covid-19 pandemic. Although there are quite a number of studies that have had a pandemic impact on health workers, there is still a lack of research showing the coping strategies of health workers to continue serving patients, especially in Indonesia. In this study, the number of participants as many as 56 health workers who were active during the Covid-19 pandemic were given one open question; “whatever you do to keep serving patients” which was then compiled by the researcher and processed into 10 main themes. Based on the qualitative analysis, the researcher found that the theme of taking care of oneself first and the meaning of life at work had a higher percentage than other themes. Further research is expected to provide assistance from the environment to support the management strategies of health workers working on the front lines.